Family Characteristics as Correlates of Academic Performance among School Children in Fishing Settlements in Nigeria: Karakteristik Keluarga sebagai Korelasi Prestasi Akademik Anak Sekolah di Permukiman Nelayan di Nigeria - Oni, Adesoji Adeolu; Olaniran, Olakunle Lateef (Universitas Muhammadiyah Sidoarjo, 2018)
In all societies, the family is the premier institution for the socialization of children, adult intimate relationship, life-long economic support and occupation and continuity of relationship along the life course. Scholars had argued for and against the fact that there is a strong relationship between family characteristics and children educational success or otherwise. This present study investigate family characteristics as correlates of academic performance among school children in fishing settlements of Ogun state, Nigeria. A descriptive research design was adopted. The target population comprisedall JSS2 students in Ogun water side local government area of Ogun state. Three null hypotheses were tested at 0.05 level of significance. The samples comprised of 400 respondents and 8 junior secondary schools. Multistage sampling techniques were adopted. A self-designed questionnaire was used to collect relevant data. Data generate were analyzed using frequency count, simple percentage, mean, standard deviation and one-way analysis of variance (ANOVA).Recommendations were made that there should be increase cooperation between the parents/ guardians and the school. Quality assurance unit of policy makers should ensure regular monitoring of school particularly in the area of teaching learning process.